Step
*
1
of Lemma
ps-sigma-elim-unelim
1. C : SmallCategory
2. X : ps_context{j:l}(C)
3. A : {X ⊢ _}
4. B : {X.A ⊢ _}
5. I : cat-ob(C)
6. x : X.Σ A B(I)
⊢ (SigmaUnElim o SigmaElim I x) = (1(X.Σ A B) I x) ∈ X.Σ A B(I)
BY
{ ((RepUR ``psc-adjoin`` -1 THEN D -1) THEN RepUR ``presheaf-sigma`` -1 THEN D -1) }
1
1. C : SmallCategory
2. X : ps_context{j:l}(C)
3. A : {X ⊢ _}
4. B : {X.A ⊢ _}
5. I : cat-ob(C)
6. alpha : X(I)
7. u : A(alpha)
8. x2 : B((alpha;u))
⊢ (SigmaUnElim o SigmaElim I <alpha, u, x2>) = (1(X.Σ A B) I <alpha, u, x2>) ∈ X.Σ A B(I)
Latex:
Latex:
1.  C  :  SmallCategory
2.  X  :  ps\_context\{j:l\}(C)
3.  A  :  \{X  \mvdash{}  \_\}
4.  B  :  \{X.A  \mvdash{}  \_\}
5.  I  :  cat-ob(C)
6.  x  :  X.\mSigma{}  A  B(I)
\mvdash{}  (SigmaUnElim  o  SigmaElim  I  x)  =  (1(X.\mSigma{}  A  B)  I  x)
By
Latex:
((RepUR  ``psc-adjoin``  -1  THEN  D  -1)  THEN  RepUR  ``presheaf-sigma``  -1  THEN  D  -1)
Home
Index